Analisis Motivasi Mahasiswa dalam Memilih Program Studi Farmasi sebagai Pilihan Karier - Ramadhani, Berliana Ajeng; Pratama, Aurelia Ghina; Ramadhan, Rizkia Linda Lintang (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This article aims to examine the selection of a study program is a crucial step for students, because it will have an impact on the direction of education and career in the future. The Pharmacy Study Program is one of the preferred choices because it provides many career paths, including pharmacies, hospitals, the pharmaceutical industry sector, and drug research. This research aims to investigate the reasons behind the choice of the Pharmacy Study Program by students as their career path. The methodology used in this study is a descriptive quantitative approach with the distribution of questionnaires using a Likert scale of 1-5 to students who are active in the Pharmacy study program. The data obtained were analyzed descriptively to recognize the main motivational factors, which consisted of academic, career, social, practical, and personal motivation. The findings of this study show that students decide to choose Pharmacy due to a combination of internal factors, such as interest in pharmaceutical science and personal goals, as well as external factors, such as support from family, promising job prospects, and internship experience. The results of this research are expected to serve as a reference for educational institutions in improving academic guidance and delivering accurate information to prospective students.